MACEDONIA IS OURS, BUT... (Annual of the Faculty of Philosophy in Skopje, 2009)
The article focusese on the views of greek intellectuals, politicians and diplomats about Macedonian ancient past and macedonian populations before WWL It is very interesting to note that we can find views which did not correspond with the official position of greek state and intellectual ellite, even among the books of Kazazis, distinguished Greek nationalist and rector of the University in Athens.